Telemedicine Medical Screening Evaluation Expedites the Initiation of Emergency Care for Children. Issue 7 (12th July 2021) - Friedman, Jonathan; Lame, Maria; Clark, Sunday; Gogia, Kriti; Platt, Shari L.; Kim, Ji Won
Abstract : Supplemental digital content is available in the text. Abstract : Objective: Prior studies show that staffing a physician at triage expedites care in the emergency department. Our objective was to describe the novel application and effect of a telemedicine medical screening evaluation (Tele-MSE) at triage on quality metrics in the pediatric emergency department (PED). Methods: We conducted a retrospective quasi-experimental pre-post intervention study of patients presenting to an urban PED from December 2017 to November 2019 who received a Tele-MSE at triage. We analyzed 4 diagnostic cohorts: gastroenteritis, psychiatry evaluation, burn injury, and extremity fracture. We matched cases with controls who received standard triage, from December 2015 to November 2017, by age, diagnosis, weekday versus weekend, and season of presentation. Outcome measures included door-to-provider time, time-to-intervention order, and PED length of stay (LOS). Results: We included 557 patients who received Tele-MSE during the study period. Compared with controls, patients who received a Tele-MSE at triage had a shorter median door-to-provider time (median difference [MD], 8.4 minutes; 95% confidence interval [CI], 6.0–11.0), time-to-medication order (MD, 27.3 minutes; 95% CI, 22.9–35.2), time-to-consult order (MD, 10.0 minutes; 95% CI, 5.3–12.7), and PED LOS (MD, 0.4 hours; 95% CI, 0.3–0.6). Conclusions: A Tele-MSE is an innovative modality to expedite the initiation of emergency care and reduce PED LOS for children. This novel intervention offers potential opportunities to optimize provider and patient satisfaction and safety during the COVID-19 pandemic.